Pengaruh Kepemimpinan, Pelatihan Dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Karyawan PT.Taspen Persero KCU Semarang - Shodiq, Muhammad Yafi’; Kasmari, Kasmari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Leadership, training and HR development have an important role in improving employee performance. In achieving optimal performance, companies need to overcome various challenges that may arise in implementation. The research was conducted at PT Taspen Persero KCU Semarang, which is known to have data on leadership and training variables that affect employee performance. The research method uses descriptive quantitative with purposive sampling for the period 2024. The influence between variables is explained using multiple regression analysis. The results showed that there is a positive and significant influence between leadership, training and development of Human Resources (HR) on employee performance. In this case employees feel valued and motivated to give their best in carrying out a job.